Classical drop phase diagram and correlations in phase space - Chernomoretz, Ariel (2003)
The phase diagram of a finite, constrained, and classical system is built from the analysis of cluster distributions in phase and configurational spaces. According to the calculated critical exponents τ , and γ , three regions can be identified. One (low density limit) in which first order phase transition features can be observed. Another one, corresponding to the high density regime, in which fragments in phase space display critical behavior of 3D-Ising universality class type. An intermediate density region, in which power-laws are displayed but cannot be associated to the abovementioned universality class, can also be recognized.